Anamorphosis and seamlessness in contemporary Indigenous art. Issue 1 (2nd January 2017) - Rowe, Astarte
Abstract : This paper develops a theoretical framework through which to assess contemporary Indigenous art, defining this emergent art form on the basis of its seamless interfacing with, and anamorphic luxation of, the global contemporary. Seamlessness and anamorphosis are core organizing methodologies for tracking this art form's response to its institutionalization within a global arts system. Derrida's theory of the tympan is used to assess the sublating logic of the global contemporary, as well as to provide a basis for understanding how the artworks in question feed into this logic through oppositional modes of resistance. When theatricalized, however, the seamlessness of such artworks not only offers a critical perspective on the irresolvability of New World occupation; seamlessness also becomes a crucial threshold for understanding what is at stake in the global contemporary – that is, the suturing of externality to the world. Contemporary Indigenous art is as involved in laying bare the axiomatic of the global contemporary as it is about intensifying what exceeds this axiomatic – that is, an Indigenous relation to an externally oriented outside. This non-metaphysical relation to the outside is expressed through key structural elements of anamorphosis: its immanence to the picture plane, yet its unassignable coordinates therein. Anamorphosis is appended to Deleuze and Guattari's geophilosophical theorization of the local absolute in order to supply a reading of contemporary Indigenous artworks as the projection of an unsublatable outside – an outside that, by expressing itself in localities, opens up this relation beyond any system, logic, or codification. Could one envision a conceptual alliance between Indigeneity and geophilosophy, prefigured through the very seamlessness and anamorphosis at work in contemporary Indigenous art?